CONSEQUENCES OF THE MANAGEMENT OF SOLID HOUSEHOLD WASTE ON THE ENVIRONMENT AND HUMAN HEALTH IN THE MUNICIPALITY OF ALLADA IN BENIN - CLEDJO, Placide; Glito, Michaël Serge G. (My University, 2020)
The present survey identifies the consequences of the mechanism of management of the strong and domestic garbage on the health human of the populations and the environment in the Township of Allada.The works of land partners to the documentary research permitted to know how to become him of the domestic strong garbage of Allada and his/her/its risks on the environment and the human health. The PEIR model has been used for the analysis of the results.The results show that the households constitute the big sources of production of the garbage with 55% of no degradable nature, 43 % biodegradable nature, and 2 % of dangerous. The commercial activities constitute the second sources of production that are largely of biodegradable nature (70 %), according to people investigated. Besides, the main fashions of management adopted by (82 %) of the populations investigated are the dismissal on the garbage dumps savage, the wild incineration and the burying. He/it is also noted in the middle a weak rate of subscription of the households investigated (20 %) to the structures of precollection
Keywords: Allada; consequences; Management of the garbage; impact; environment